Results of Early Childhood Activities with a STEM Education Model in Conjunction with Sufficiency Economy for Developing Intellectual Skills - Junjumnong, Natchana; Pongpisanu, Sudaporn; Sumbandit, Weena (Saengtham College Journal, 2026)
This research aims to develop the results of organizing early childhood activities with the STEM education model combined with Sufficiency Economy to develop intellectual skills with the objectives: 1. To study the results of organizing activities for early childhood children with a STEM education model together with the sufficiency economy to develop intellectual skills. 2. To compare intellectual skills results before and after organizing early childhood activities with a STEM education model together with the sufficiency economy. To develop intellectual skills understanding of learning management in early childhood activities with a STEM education model combined with Sufficiency Economy to develop intellectual skills after comparing with the 70 percent criteria. The sample group used in this research includes male and female early childhood children who are studying in kindergarten 3, semester 2, academic year 2023 at Prakumarn Surin School. Surin Province Obtained by purposive sampling, 1 room with 30 students for use in the experiment of organizing early childhood activities. With a STEM education model combined with Sufficiency Economy to develop intellectual skills. Research tools in this research are the early childhood activity department with a STEM education model combined with Sufficiency Economy to develop intellectual skills and testing to develop intellectual skills. The results of the research found that early childhood children were taught STEM education together with the Sufficiency Economy to develop intellectual skills and have basic skills to develop after the experiment higher than before the experiment with statistical significance at the .01 level.